A strategy for quality evaluation of complex herbal preparations based on multi-color scale and efficacy-oriented high-performance thin-layer chromatography characteristic fingerprint combined with chemometric method: Sanwujiao Pills as an example - Wenhan Pei; Yufeng Huang; Yuan Qu; Xiuming Cui; Liqin Zhou; Hongfang Yang; Mingshun Zhao; Zhifeng Zhang; Fan He; Hua Zhou (Heliyon, 2023)
To rapidly evaluate the quality of complex herbal preparations, a new strategy was proposed based on multi-color scale and efficacy-oriented high-performance thin-layer chromatography (HPTLC) characteristic fingerprint combined with chemometric method. Firstly, effective components were screened through high-performance liquid chromatography with ultraviolet detection and evaporative light-scattering (HPLC-UV-ELSD), using multi-wavelength fusion combined with network pharmacology and molecular docking techniques. Subsequently, guided by the effective components, the targeted HPTLC characteristic fingerprint was established by multi-color scale scanning. Finally, combined with the chemometric method, the consistency of the preparation quality was evaluated, the marker components leading to quality differences were screened, and the quality control limit was established. Sanwujiao Pills (SWJPs) is a herbal preparation composed of six herbs for treating rheumatoid arthritis (RA). Through this strategy, four HPTLC characteristic fingerprints were established, they were derived from five herbs and guided by eight effective components in SWJPs. Through similarity, clustering heatmap, principal component analysis (PCA), and orthogonal partial least squares discriminant analysis (OPLS-DA), the quality distinctions among the 12 batches of SWJPs were determined. These batches were categorized into two groups based on their production time, and eight components affecting the quality of the preparation were identified. Meanwhile, the quality control threshold for SWJPs was determined based on Hotelling's T2 and DModX methods. This strategy aims to rapidly evaluate the quality of complex herbal preparations by HPTLC and extends the application of HPTLC fingerprint chromatography for identifying herbal medicine species and activity-related quality detection. The proposed strategy is also helpful for the quality control of other complex herbal preparations.